2021
DOI: 10.1111/ipd.12778
|View full text |Cite
|
Sign up to set email alerts
|

Parents' preferences for preventive and curative dental services: A comparison between fissure sealant and composite filling using willingness‐to‐pay method

Abstract: Health-related resource-allocative decisions are difficult to make, particularly in the oral health field where demands for services are beyond the capacities of health systems, especially in low-and middle-income countries. 1 For an evidencebased medical decision making, in addition to sound and clear evidence of the effectiveness of health services and clinical expertise, patient's preferences should be taken into account. 2 Moreover, priorities and demand for health care, as part of social services, need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Providing public oral health prevention care and increasing their awareness of its advantages is required for this group. Our finding indicated that having dental insurance increases the tendency for preventive care, like studies in Greek and the United States [32,34], but the insurance type was not considered an influential factor, similar to Saadatfar's study in Iran [15].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Providing public oral health prevention care and increasing their awareness of its advantages is required for this group. Our finding indicated that having dental insurance increases the tendency for preventive care, like studies in Greek and the United States [32,34], but the insurance type was not considered an influential factor, similar to Saadatfar's study in Iran [15].…”
Section: Discussionsupporting
confidence: 86%
“…From the results, it is clear that most of the participants were in favor of treatment like in previous studies in Iran [ 15 ] and Bulgaria [ 29 ]. In contrast, in a study in Southern Thailand, parents' willingness to pay for sealants and fillings was not significantly different [ 30 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This method evaluates the Willingness to Pay (WTP), which is "the maximum amount of monetary value that an individual would be willing to sacrifice to obtain the benefit of that healthcare service," through questionnaires or face-to-face interviews based on a hypothetical scenario regarding the healthcare service [12][13][14]. Several studies have reported on WTP for dental treatments, including preventive treatment of dental caries [15,16], periodontal disease [17], dental implant treatment [18,19], and orthodontic treatment [20]. The findings of studies on WTP can be used to perform economic evaluations of desired healthcare services by the general population and are expected to be a resource for policy planning regarding oral health [13].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of studies on WTP can be used to perform economic evaluations of desired healthcare services by the general population and are expected to be a resource for policy planning regarding oral health [13]. As such, several dental WTP studies have demonstrated the distribution of WTP values to dental healthcare services based on the responses of survey participants and have shown that high/low WTP values are associated with individual characteristics such as socioeconomic status [13,[15][16][17][18]20].…”
Section: Introductionmentioning
confidence: 99%